Rabies antigen spread amongst apparently healthy dogs in Nigeria: a review (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
Rabies with a timeline history of over 2300 years BC is 100% preventable. Yet over 55,000 people are reported dead annually due to rabies. Most of the deaths are in the developing countries, India and Africa. In Nigeria, the first officially documented report of human rabies was in 1912 and that of canine rabies was in 1925. The long history of rabies and the evidences of its endemicity have been found in all native dialects in Nigeria that described only the violent rabies. Researchers over the years have reported the presence of rabies virus antibodies in over 15.93 to 30.7% of unvaccinated dogs and humans respectively, in south western part of Nigeria. Of recent, researchers in Nigerian Universities and Research Institutes are experiencing and reporting cases of the presence of rabies virus antigen in the brains of apparently healthy dogs and even in the wild life across the country. Some studies of the prevalence of rabies antigens in the brain and saliva of apparently healthy dogs slaughtered for human consumption in Nigeria; revealed a 28% consumed dogs in N/west, 31% – 44% from N/east and 24% from N/central tested positive for rabies antigen in their brain. Similarly, 6%-8% of the dogs had rabies antigen in their saliva at the point of slaughter. In wildlife brain tested for rabies antigen revealed prevalence in mongoose to be 11%, jackals 9%, squirrels 8.3%, hydrax link 17% and wild cats 16%. The intent of this review is to bring into focus the prevailing carrier status of high percentage of Nigerian dogs and wildlife and its possible consequences on human before the rabies interest groups of the international community. This is with a view to open facets for discussion and understanding the epidemiology of rabies and to seek for further collaboration on the situation of rabies in Nigeria. It may necessitate drawing new protocol for human prophylaxis following bite from apparently healthy dogs.